Analisis Kinerja Jaringan LAN Di Laboratorium Komputer SMK Wiyata Satya Menggunakan Metode Qualiy Of Service - Rifal Pratama Putra (Pusat Riset dan Inovasi Nasional, 2024)
The rapid advancement in information technology, particularly in the realm of internet networks, has become an integral part of various aspects of modern life. The quality of internet networks has emerged as a pivotal aspect in facilitating swift information access and efficient data exchange across corporate, governmental, higher education, and school settings. This research aims to evaluate the performance of the Local Area Network (LAN) at the Computer Laboratory of SMK Wiyata Satya by employing the Quality of Service (QoS) method. The QoS method is utilized to manage key parameters within the network, such as bandwidth, throughput, jitter, packet loss, and latency. The primary focus of this study lies in identifying issues within the network, including connectivity difficulties and disruption in connections that can impact user experience. This study is crucial because internet technology plays a vital role in enhancing students' learning experiences in educational settings. Evaluating LAN network performance is critical in ensuring that modern education harnesses internet technology effectively. The outcomes of this research are anticipated to provide profound insights into potential solutions to enhance the quality of internet networks in educational environments, thereby supporting a superior learning experience for students.